The evolution of clinical periodontal therapy. - (:unkn) unknown (My University, 1994)
Periodontal diseases are considered as old as the history of mankind, Magical, religious and herbal treatments were demonstrated in almost all of the early writings. However, methodical, carefully reasoned therapeutic approaches did not exist until the middle-ages and modern treatment with a scientific base and sophisticated instrumentation did not develop until the 18th century. Prior to the 1950s, diseases were mostly treated by root debridement and the extraction of the affected teeth. Until the 1970s, it was primarily the symptoms of periodontal diseases that were treated. The goal was radical elimination of the periodontal pocket (resective therapy). The means were gingivectomy, flap procedures and osseous surgery. The disadvantages were the massive sacrifice of periodontal tissues, lack of regeneration and clinically elongated teeth. These disadvantages, along with the realization of the importance of aetiologic agents, raised questions about the necessity of total pocket elimination, and the control of subgingival infection by a thorough scaling and root planing (nonsurgical therapy), with and without antibiotics, became a commonly used treatment during the 1980s. Comparative longitudinal studies, surgical versus nonsurgical, demonstrated that both surgical and nonsurgical therapy result in limited regeneration and healing with a long junctional epithelium. The most important aspects of today's modern concept of periodontal therapy are causal, regenerative, and specific for disease type and severity. Although the regeneration of the periodontium can be accomplished with the biological principles of guided tissue regeneration and graft materials, compared to conventional methods, the restoration of a completely normal periodontal status has not yet been achieved. We are about to reach our ultimate goals and presently, the more promising research directions for a substantial regeneration seems to lie in biological mediators. Although the future of periodontal therapy is bright, it is still of critical importance to have a preventive strategy to keep individuals healthy beforehand.